Unusual manifestation of gastric mucormycosis in a patient with rheumatoid arthritis - Milić Perović, Marija; Šolajić, Nenad; Vučković Hardi, Lidija; Knežević Ivanovski, Tamara; Juloski, Jovan (Vojnosanitetski pregled, 2022)
Introduction. Mucormycosis is a life-threatening opportunistic infection whose incidence has significantly risen during the last two decades. The gastrointestinal form is very rare, with the stomach as the most common site of infection, followed by the colon and ileum. Risk factors include uncontrolled diabetes mellitus, corticosteroid use, and organ transplantation. We report a patient with a history of rheumatoid arthritis who has developed gastrointestinal mucormycosis. To the best of our knowledge, this is the first such case reported in the literature. Case report. A 53-year-old female patient with a prior medical history of rheumatoid arthritis was admitted to the hospital due to persisting diarrhea. Physical examination revealed diffuse abdominal tenderness to palpation without meteorism and peritoneal signs. Laboratory results demonstrated systemic inflammation, so antibiotic therapy was administered. Abdominal computed tomography findings revealed inflammation of the rectum and the left colon. Colonoscopy findings were indicative of Crohn’s disease. Additionally, the patient had developed profuse rectal bleeding and consequently underwent emergency surgery. Subtotal colectomy with ileostomy and partial gastrectomy was performed. The patient’s condition rapidly worsened after the operation, and she died due to multi-organ failure. Histologic findings of resection specimens discovered chronic active colitis and extensive gastric necrosis associated with dense mixed inflammatory infiltration and numerous non-septate and 90-degree branching hyphae. Diagnosis of invasive gastric mucormycosis was obtained, but unfortunately, several days after the patient’s death. Conclusion. It is very important to obtain high awareness among clinicians of this deadly infection to achieve a prompt diagnosis and effective therapy.
Keywords: arthritis, rheumatoid; diagnosis; diagnosis, differential; digestive system; histological techniques; mucormycosis